Phytochemical and Biological Investigations of Eurya acuminata (Theaceae) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The methanol extract of the powdered leaf of Eurya acuminata was investigated for isolation of secondary metabolites and two compounds were obtained by using VLC, column chromatography and TLC. The compounds were identified as phytol (1) and ?-sitosterol by extensive spectroscopic studies, including high field NMR analyses as well as co-TLC with authentic samples. The methanol extract of leaf of E. acuminata and its organic and aqueous soluble partitioning materials were evaluated for cytotoxic, thrombolytic and antimicrobial properties. In the cytotoxicity study the aqueous fraction of crude methanolic extract showed significant lethality towards brine shrimp having LC50 value 8.821 ?g/ml as compared to standard vincristine sulfate (0.404 ?g/ml). In the study for thrombolytic property, different extract of E. acuminata exhibited various thrombolytic activity ranging from 13.66 to 31.89 % as compared to standard streptokinase (46.51 %). No antimicrobial activity was observed from leaf extracts.Dhaka Univ. J. Pharm. Sci. 15(2): 151-154, 2016 (December)